SUBTRACTION SCHEMES FOR THE THERMAL CONDUCTIVITY EQUATION - Nuraliyev, T; Alimov, S; Khamdamov, F (Science technology&Digital finance, 2023)
In the same-sex environment, heat transfer nets for one dimension have been constructed and studied.